Virtual Works – Actual Things - Goehr, Lydia; Davie, David; Kiloh, Kathy; McNulty, Jake; Hindrichs, Gunnar; Rink, John (Leuven University Press, 2021)
"Beyond musical works: new perspectives on music ontology and performance What are musical works? How are they constructed in our minds? Which material things allow us to speak about them in the first place? Does a specific way of conceiving musical works limit their performative potentials? Which alternative, more productive images of musical work can be devised?